Nonlinearities, Business Cycles and Exchange Rates - Chinn, Menzie D. (My University, 2008)
The paper brings together the literature on exchange rate models and monetary policy models, with special reference to the importance of output, inflation gaps and exchange rate targets. It focuses on the dollar/euro exchange rate, and the differential results arising from using alternative measures of the output gap for the United States and the euro region.